Support-Seeking Strategies and Social Support Provided in Chinese Online Health Communities Related to COVID-19 - Liu, Yi; Zhu, Yiwei; Xia, Yixuan (Frontiers in Psychology, 2021)
Online health communities have become one of the most important means for people to seek social support during the coronavirus 2019 disease (COVID-19) pandemic. This study details content analysis of support-seeking strategies and social support offered on the online forum “Baidu COVID-19bar” across different stages of initial stage as well as during the entire initial stage of the COVID-19 pandemic. The results show that asking for support and disclosing directly were the main strategies used across the different stages and during the entire initial stage. Informational support and emotional support were the most common types sought in the first two stages and the entire initial stage, and informational support was the main type during the decline stage. Furthermore, asking for support was more likely to elicit informational support while disclosing directly was more likely to elicit emotional support. Theoretical and practical implications of the findings are discussed.